A founder variant in the South Asian population leads to a high prevalence of FANCL Fanconi anemia cases in India. Issue 1 (26th September 2019) - Donovan, Frank X.; Solanki, Avani; Mori, Minako; Chavan, Niranjan; George, Merin; C, Selvaa Kumar; Okuno, Yusuke; Muramastsu, Hideki; Yoshida, Kenichi; Shimamoto, Akira; Takaori‐Kondo, Akifumi; Yabe, Hiromasa; et al.
Abstract: Fanconi anemia (FA) is a rare genetic disorder characterized by bone marrow failure, predisposition to cancer, and congenital abnormalities. FA is caused by pathogenic variants in any of 22 genes involved in the DNA repair pathway responsible for removing interstrand crosslinks. FANCL, an E3 ubiquitin ligase, is an integral component of the pathway, but patients affected by disease‐causing FANCL variants are rare, with only nine cases reported worldwide. We report here a FANCL founder variant, anticipated to be synonymous, c.1092G>A;p.K364=, but demonstrated to induce aberrant splicing, c.1021_1092del;p.W341_K364del, that accounts for the onset of FA in 13 cases from South Asia, 12 from India and one from Pakistan. We comprehensively illustrate the pathogenic nature of the variant, provide evidence for a founder effect, and propose including this variant in genetic screening of suspected FA patients in India and Pakistan, as well as those with ancestry from these regions of South Asia.